Pelatihan Konsep Audio Visual Dalam Pengembangan Budaya Melayu Di Desa Tualang - Jefrizal Jefrizal; Iik Idayanti; Ridwan Ridwan (Fakultas Ilmu Budaya Universitas Lancang Kuning, 2020)
The purpose of this training is to provide an understanding of general audio-visual information and give tips to explore ideas from the potential of local art and culture content to be developed into content on social media. To achieve this, stages are needed, including exposure to general audio-visual information and exposure to tips to explore ideas from the potential of local art and culture content.